2008
DOI: 10.1007/s00449-008-0269-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of mannitol production using cashew apple juice as substrate

Abstract: The use of agriculture excess as substrate in industrial fermentations became an interesting alternative to reduce production costs and to reduce negative environmental impact caused by the disposal of these products. In this work, a kinetic study of mannitol production using cashew apple juice as substrate was studied. The carbohydrates of cashew apple juice are glucose and fructose. Sucrose addition favored the yield of mannitol (85%) at the expense of lower productivity. The best results were obtained apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…The results showed that the CAJ was very high in reducing sugars (805 g/l). The observation is similar to the value of 788 g/l reported by Osho [22] but different from the observed values of 90.45 and 100.23 g/l by Honorato et al [21] and Fontes et al [23] , respectively. Also, the values of pH, total nitrogen and crude protein of the CAJ observed in this present work were comparable to the reported values by Osho [22] .…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…The results showed that the CAJ was very high in reducing sugars (805 g/l). The observation is similar to the value of 788 g/l reported by Osho [22] but different from the observed values of 90.45 and 100.23 g/l by Honorato et al [21] and Fontes et al [23] , respectively. Also, the values of pH, total nitrogen and crude protein of the CAJ observed in this present work were comparable to the reported values by Osho [22] .…”
Section: Resultscontrasting
confidence: 66%
“…These observtions may be attributed to the location where the cashew apple fruits were obtained. Whereas cashew apple fruits used in this work and that of Osho [21] were obtained from Nigeria, Honorato et al [21] and Fontes et al [23] worked with ones obtained from Brazil. The total tannin detected in the CAJ used was very low; hence there was no need to clarify the juice before use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cashew apples can be consumed as juice, jams, and other food stuffs, the cashew tree cultivation is an agricultural activity directed at the production of the cashew nuts. Due to its large availability and low cost, cashew apple has been studied as a substrate for fermentative and enzymatic processes for several applications [16][17][18][19][20]. As such, cashew apple is considered an agricultural residue rich in reducing sugars (fructose and glucose), vitamins, minerals, and some amino acids [21] and can be a suitable low cost substrate for anaerobic digestion studies.…”
Section: Cashew Apple Wastementioning
confidence: 99%
“…It is rich in reducing sugars such as fructose, glucose, sucrose, vitamins, minerals, and some amino acids [14]. Thus, the rich juice has been investigated for its possible use as carbon source in several fermentation processes such as in production of single cell protein [14,15], wine [15], mannitol [16,17], biosurfactant [18], lactic acid [16], and oxalic acid [19]. The use of the juice for these purposes may serve as a means of dealing with the problem of spoilage and underutilization after collecting the nuts, which is the main reason for cashew production.…”
Section: Introductionmentioning
confidence: 99%